2011
DOI: 10.1186/1746-160x-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age, impaction types and operative time on inflammatory tissue reactions following lower third molar surgery

Abstract: BackgroundPostoperative mobidity following third molar surgery is affected by a number of factors. The study of these factors is essential for effective planning and limitation of morbidity. The aim of this study was to determine the effect of age, type of impaction and operative time on immediate postoperative tissue reactions following mandibular third molar surgery.MethodsConsecutive patients with impacted mandibular third molar teeth were studied. All the third molars were classified according to Winter's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
4
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 20 publications
7
86
4
10
Order By: Relevance
“…This is in contrast to the findings of Bello SA et al, [15], Baqain ZH [7], suggested that post-operative morbidity increases significantly with age progression. However, there is reduction in resiliency of bone as age increases but it is not found significantly related to any variable of this study.…”
Section: Methodscontrasting
confidence: 56%
“…This is in contrast to the findings of Bello SA et al, [15], Baqain ZH [7], suggested that post-operative morbidity increases significantly with age progression. However, there is reduction in resiliency of bone as age increases but it is not found significantly related to any variable of this study.…”
Section: Methodscontrasting
confidence: 56%
“…The increased surgical difficulty is directly proportional to the increase in postoperative pain and inflammation. 32,33 Although some studies reported increased surgical difficulty and/or root fractures in rats receiving chronic treatment with alendronate sodium, there was no significant difference in surgical difficulty parameters in this study. This suggests that all groups were subjected to similar surgical stress.…”
Section: Discussionmentioning
confidence: 60%
“…Swelling was evaluated using a measuring tape by a modification of a 3 line measurements using 5 fixed points on surgical side of the face and finding the average as described by Bello et al [2]. The fixed points used were A; the most posterior point at the midline on the tragus, B; lateral canthus of the eye, C; the most lateral point on the corner of the mouth, D; soft tissue pogonium which is the most prominent point at the midline on the chin and E; most inferior point on the angle of the mandible.…”
Section: Methodsmentioning
confidence: 99%
“…Sequentially, there is a release of mediators from mast cells, the vasculature and other cells. Histamine and serotonin appear first, followed by bradykinin and later prostaglandins and other eicosanoids [2].…”
Section: Introductionmentioning
confidence: 99%